Assessing Vulnerability to Climate-Induced Humanitarian Crises: A Global Perspective - Marsono Marsel Sihotang; Hoddinott Hoddinott; Rogers Rogers (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2022)
This research offers a comprehensive analysis of vulnerability to climate-induced humanitarian crises on a global scale. In a world increasingly impacted by the ramifications of climate change, understanding vulnerability becomes paramount. The study delves into the intricate web of factors that contribute to vulnerability, ranging from socio-economic disparities and healthcare infrastructure to environmental degradation and access to resources. Through a multidisciplinary approach, it identifies regions and populations most at risk, emphasizing the disproportionate burden borne by marginalized communities. The research underscores the urgency of proactive adaptation strategies, from climate-resilient infrastructure to community-based initiatives, and highlights the critical role of international cooperation. By providing evidence-based insights and policy recommendations, this research equips policymakers, humanitarian organizations, and communities with the tools needed to mitigate vulnerability, enhance resilience, and work collectively toward a more sustainable and equitable future in the face of a changing climate.